Unmasking Vibrio vulnificus: Emerging “flesh-eating bacteria” and its health implications - Galo Guillermo Farfán-Cano (School of Medicine, Universitas Syiah Kuala, 2023)
Recent media reports in the USA have raised concerns about dubbing Vibrio vulnificus as the